Perancangan Sistem Informasi Klinik Berbasis Web Menggunakan Bahasa Pemrograman PHP dan Database MySQL - Hari Setiyani; Rizky Adiputra (JI-Tech, 2020)
At this time Outpatient Clinic founded by owner Pharmacy Cipete Raya still using the manual system, a manual system here means a system that still uses hand writing method without the slightest untouched computer technology. This will only slow the duty employees, for example in the case of registration of the patient's identity because the recording was done with the registration handwritten method. As well as the doctor has a problem with the service outside working hours so that the doctor did not recall any patient who has treated him.In this study aninformation system will be built using a web-based online publication that media will be built, is designed such that it can process data, storage of data, and disseminate information quickly and accurately is intended only for within the scope of the Clinic.